THE CONTRIBUTION OF SMALL AND MEDIUM ENTERPRISES (UMKM) TO ECONOMIC GROWTH IN BANTEN PROVINCE - Nely Hartika; Suwatno Suwatno; Hari Mulyadi (Green Publisher, 2023)
Small and medium enterprises (UMKM) are the most strategic national economic sector that concerns the livelihoods of many people, thus becoming the backbone of the national economy. The Indonesian economy has proven to be a safety valve for the national economy during times of crisis, as well as a dynamo for economic growth after the economic crisis. This study aims to determine the contribution of UMKM to economic growth in Banten Province. This is a qualitative study with the research location in Banten Province. The data sources for this study are primary data obtained directly through interviews with UMKM actors in Banten Province, and secondary data obtained through articles, books, and references related to the problem of UMKM's contribution to economic growth. Data collection techniques use interviews and documents. Data analysis techniques use three adopted stages: reduction, data presentation, and verification. The results of this study are that the contribution of UMKM to economic development can be through UMKM's contribution to the formation of GDP/GDRP, UMKM's contribution to job creation to measure poverty, contributions to exports that are useful for measuring the competitiveness of local UMKM, the role of UMKM in investment, and entrepreneurship